Davi Nascimento: Uncertain dawn, equilibrian presence on the wire of the letter (TEL Tempo, Espaço e Linguagem, 2023)
Davi Nascimento was a black man, a lyrical artist, traversed by psychic suffering and its stigmatizations. Moved by the video art Davi – Alvorada Incerta (Ana Pedrosa, 2021), we think about his poetics, guided by counter-colonial operators, to think about the lyrics as gesture, vocality, language, memory, ancestry, production of meanings and inscription of life, in a world where its presence has been violated.